AI-Assisted Project-Based Language Learning in Indonesian Secondary Education: Enhancing Literacy and 21st-Century Competence - Taufik, Taufik; Bulan, Arif; Hasan, Hasan; Marlina, Leni (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
The Society 5.0 era requires language education that integrates digital technology with humanistic, learner-centered pedagogy; yet in many Indonesian rural junior secondary schools, instruction remains lecture-dominated, literacy is confined to technical reading and writing, and the integration of artificial intelligence (AI) into Project-Based Language Learning (PBLL) is still underexplored. This study aims to explore how AI-based tools are integrated into PBLL to support literacy and 21st-century competence in Indonesian language instruction at SMPN 2 Woja, Dompu Regency. Employing a qualitative case study design, data were collected over three months (April–June 2025) through participatory observation (12 sessions), in-depth and focus group interviews, and documentation analysis. Participants, selected purposively, were one Indonesian language teacher, 28 eighth-grade students, and the school principal. Findings are reported as descriptive, context-bound evidence rather than causal proof. Four key results emerged: (1) AI tools such as Grammarly, Speech-to-Text, automated feedback, and educational chatbots were integrated as complements across pre-project, development, and revision phases; (2) students showed noticeable improvement in narrative and expository writing, with 21 of 28 students (75%) reaching the proficiency threshold in the final project assessment; (3) students responded positively, reporting increased motivation, autonomy, and metacognitive awareness, while voicing concerns about over-reliance; and (4) the teacher's role shifted from information provider to learning facilitator. Challenges included uneven digital literacy and limited infrastructure. The study concludes that AI-assisted PBLL is a feasible, humanistic model for Indonesian secondary language education, and recommends that teachers adopt it gradually, schools invest in infrastructure and sustained professional development, and policymakers embed equitable, ethical AI guidance within the Kurikulum Merdeka framework.